2015
DOI: 10.1002/cncr.29682
|View full text |Cite
|
Sign up to set email alerts
|

Use of the lung cancer–specific Quality of Life Questionnaire EORTC QLQ‐LC13 in clinical trials: A systematic review of the literature 20 years after its development

Abstract: 13 (QLQ-LC13) covers 13 typical symptoms of lung cancer patients and was the first module developed in conjunction with the EORTC core qualityof-life (QL) questionnaire. This review investigates how the module has been used and reported in cancer clinical trials in the 20 years since its publication. Thirty-six databases were searched with a prespecified algorithm. This search plus an additional hand search generated 770 hits, 240 of which were clinical studies. Two raters extracted data using a coding scheme.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 239 publications
(217 reference statements)
0
43
0
6
Order By: Relevance
“…Again, these are knowledge transfer concerns requiring intervention to improve reporting practices and to ensure PRO results are interpreted accurately so they can appropriately inform patient care. Recent reviews confirm that reporting of PRO endpoints remains unsatisfactory overall; particularly regarding the reporting of PRO hypotheses, methodology, missing data, and generalisability of results [19][20][21][22][23][24][25][26]. Failing to report this information is wasteful as it limits the potential for readers to appraise the effect of interventions on patient health status, and the potential for PRO systematic reviews to impact clinical recommendations and health policy [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Again, these are knowledge transfer concerns requiring intervention to improve reporting practices and to ensure PRO results are interpreted accurately so they can appropriately inform patient care. Recent reviews confirm that reporting of PRO endpoints remains unsatisfactory overall; particularly regarding the reporting of PRO hypotheses, methodology, missing data, and generalisability of results [19][20][21][22][23][24][25][26]. Failing to report this information is wasteful as it limits the potential for readers to appraise the effect of interventions on patient health status, and the potential for PRO systematic reviews to impact clinical recommendations and health policy [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently used PRO to assess HRQoL was the EORTC QLQ-C30 core cancer instruments, the lung cancer specific module the EORTC QLQ-LC13, LCSS, and EQ-5D. The EORTC instruments, while considered by some authors as the standard for HRQoL measurement in lung cancer (Koller et al, 2015), were developed prior regulatory PRO guidance. The LCSS appears to be face and content valid for this patient population (Hollen et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A review of literature summarizing the use of the EORTC QLQ-LC13 in clinical trials supports this finding, reporting that of the 109 trials found to have included the instrument, 83 reported results and only 69 publications (63%) provided numerical values (Koller et al, 2015). The lack of published HRQoL data may be due to a publication bias, with researchers not publishing findings in cases where the data does not present favorable outcomes (decline in HRQoL) in relation to the treatment being investigated.…”
Section: Discussionmentioning
confidence: 82%
“…The most frequently used PRO to assess HRQoL was the EORTC QLQ-C30 core cancer instruments, the lung cancer specific module the EORTC QLQ-LC13, LCSS, and EQ-5D. The EORTC instruments, while considered by some authors as the standard for HRQoL measurement in lung cancer (Koller et al, 2015), were developed prior regulatory PRO guidance. The LCSS appears to be face and content valid for this patient population (Hollen et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation